A temperature and humidity self-adapting microcapsule, a preparation method and application thereof
Patent Information
- Application Number
- CN202611145550.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-30
AI Technical Summary
直接将二者混合掺入水泥基体,会出现分层、团聚、功能相互抵消等问题,无法同时发挥温湿度调控作用
温湿度双调控,功能协同增效:通过四层核壳结构设计,内层疏水相变材料调控温度,外层亲水吸湿剂调控湿度,阻隔壳层实现两相隔离,解决了亲水与疏水材料无法共存的技术难题,二者功能互不干扰且协同作用,同时抑制温缩裂缝和干缩裂缝;同时PMMA牺牲层作为临时隔离屏障,在所有水相、酸碱反应完成后溶出空腔,全程保护内层相变芯和吸湿层不受外界环境影响,功能材料利用率高。
Smart Images

Figure CN122999084A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of microcapsule preparation technology, and in particular to a temperature and humidity adaptive microcapsule, its preparation method, and its application. Background Technology
[0002] Coral reef sand (calcareous sand) is the only building material that can be sourced locally in South China Sea island and reef engineering projects. However, its particles are easily broken, have abundant internal pores, and low strength. The cementitious bodies made from it have many problems such as drying shrinkage cracks, thermal shrinkage cracks, and severe seawater erosion.
[0003] Microcapsule self-healing technology is an effective way to solve the problem of cracks in cement-based materials. Most existing microcapsules are single-function, such as self-healing microcapsules containing only epoxy resin or other repair agents, or temperature-regulating microcapsules containing only phase change materials. However, coral reef sand cementitious aggregates face the dual challenges of temperature stress and humidity changes, making single-function microcapsules insufficient to meet the durability requirements of complex marine environments.
[0004] Hydrophilic hygroscopic agents (such as superabsorbent polymer (SAP) and calcium chloride) can achieve internal curing and humidity control, while hydrophobic phase change agents (such as paraffin wax and fatty acids) can achieve temperature control. However, there is a natural interface conflict between the two: the hydrophobic phase change agent will encapsulate the hygroscopic agent, rendering it ineffective, while the moisture in the hygroscopic agent will damage the stability of the phase change material. Directly mixing the two into the cement matrix will result in problems such as stratification, agglomeration, and mutual cancellation of functions, making it impossible to simultaneously achieve temperature and humidity control.
[0005] In the prior art, CN110918013B discloses a method for preparing microcapsules with arbitrary gradation, which controls the particle size distribution of microcapsules through a variable speed process. However, this method can only prepare microcapsules with a single core material and cannot achieve dual-function composite of temperature and humidity.
[0006] Furthermore, existing urea-formaldehyde resin microcapsules exhibit poor acid and alkali resistance. In acidic seawater, corrosive industrial environments, or alkaline cement matrices, the capsule walls are prone to hydrolysis and cracking, leading to premature leakage of the core material and loss of long-term repair and regulation functions. Studies have shown that the repair efficiency of ordinary urea-formaldehyde resin microcapsules is only 7.56% in a strongly acidic environment (pH=1) and only 5.74% in a strongly alkaline environment (pH=11), far from meeting the requirements for long-term service in marine engineering.
[0007] Therefore, there is an urgent need to develop a microcapsule that can simultaneously control temperature and humidity, solving the dual technical challenges of the inability of hydrophilic hygroscopic agents and hydrophobic phase change agents to coexist and the poor acid and alkali tolerance of microcapsules. Summary of the Invention
[0008] The purpose of this invention is to provide a temperature and humidity adaptive microcapsule, its preparation method and application, which can achieve crack repair, temperature control, humidity control and alkali corrosion resistance, and through the gradation ratio, it is suitable for high corrosion and long-term service scenarios on islands and reefs in the South China Sea.
[0009] To achieve the above objectives, the present invention provides a temperature and humidity adaptive microcapsule, comprising medium-diameter capsules and small-diameter capsules. The medium-diameter capsules have a particle size range of 100~300μm, and the small-diameter capsules have a particle size range of 50~100μm. Both the medium-diameter capsules and the small-diameter capsules have a four-layer core-shell structure. The four-layer core-shell structure includes, from the inside out, a hydrophobic phase change core material layer, an expansion cavity layer, a hydrophilic and moisture-absorbing intermediate layer, and an acid and alkali resistant barrier wall material layer. The volume of the expansion cavity layer is 10~15% of the total volume of the microcapsule, reserving a certain expansion space to prevent the phase change volume change from breaking the wall material.
[0010] Preferably, the hydrophobic phase change core layer comprises a phase change material, wherein the phase change material is n-octadecane; the hydrophilic hygroscopic intermediate layer comprises a hydrophilic hygroscopic agent, wherein the hydrophilic hygroscopic agent is a composite of lithium chloride and montmorillonite; and the acid and alkali resistant barrier wall material layer is a modified urea-formaldehyde resin.
[0011] Preferably, the modified urea-formaldehyde resin specifically comprises: One or more of polydopamine (PDA) and graphene oxide (GO) are coated on the outer layer of the urea-formaldehyde resin (UF) wall material; one or more of nano-SiO2 or carbon fiber are doped inside the urea-formaldehyde resin (UF).
[0012] PDA exhibits excellent physical barrier properties and chemical stability. Its catechol and amino groups can form strong hydrogen bonds and covalent bonds with the UF wall surface, resulting in strong binding force. The dense cross-linked structure of PDA can effectively block OH groups. - and H + It erodes the UF wall material while protecting the internal phase change core material and repair agent. GO's two-dimensional layered structure further extends the penetration path of corrosive media and synergistically enhances alkali resistance with PDA.
[0013] This invention also provides a method for preparing temperature and humidity adaptive microcapsules, comprising the following steps: S1. Preparation of phase change core template microspheres: Octadecylene was heated to 35-40℃ to melt, Tween 80 (emulsifier) was added, and the mixture was dispersed at 4000-6000 rpm for 8-10 min to form an O / W emulsion; melamine-formaldehyde prepolymer was added, and the pH was adjusted to 5.2-5.5 with acetic acid. Polycondensation was carried out at 60℃ and 400 rpm for 2 h. After the reaction was completed, the mixture was washed with deionized water, filtered, and vacuum dried at 40℃ to obtain phase change core microspheres with MF as the wall (as the core template). S2, PMMA sacrificial layer coating: The phase change core microspheres were immersed in a 1% SDS (sodium dodecyl sulfonate) solution to make their surface hydrophilic and adsorb surfactants; the phase change core microspheres were dispersed in deionized water, and methyl methacrylate (MMA) monomer and crosslinking agent ethylene glycol dimethacrylate (0.5wt%) were added, along with potassium persulfate initiator. The reaction was carried out at 50-55℃ for 4-6 hours. By controlling the amount of monomer and the reaction time, a PMMA sacrificial layer with a thickness of about 3-5 μm (corresponding to the subsequent cavity thickness) was obtained. After the reaction was completed, the microspheres were centrifuged, washed, and dried at 40℃ to obtain PMMA@phase change core microspheres. S3. Moisture-absorbing intermediate layer coating: Sodium-based montmorillonite is dispersed in water (solid content 5%), and lithium chloride solution (LiCl loading 25%, based on the mass of sodium-based montmorillonite) is added and stirred for adsorption for 2 hours; polyvinyl alcohol binder is added to prepare a moisture-absorbing slurry (final PVA concentration is 3wt%); PMMA@phase change core microspheres are added to the slurry and gently stirred for 30 minutes. The microspheres are collected by filtration or centrifugation and directly transferred into an HCl solution (pH 2~3) containing 2% glutaraldehyde without drying. Crosslinking is carried out at room temperature for 15 minutes, so that PVA crosslinks in situ on the surface of the microspheres to form a water-insoluble bonding network, while fixing montmorillonite and LiCl. Residual glutaraldehyde is removed by washing with anhydrous ethanol, and then vacuum dried at 40℃ to obtain moisture-absorbing intermediate layer microspheres. S4. Preparation of nano-SiO2 reinforced UF wall: Urea and formaldehyde were mixed and reacted at pH 8-9 and 70℃ for 1 h to obtain urea-formaldehyde resin prepolymer. 5% nano-SiO2 was added and ultrasonically dispersed evenly. Moisture-absorbing intermediate layer microspheres were added to the prepolymer, stirred and dispersed, and the pH was slowly adjusted to 2.5 with hydrochloric acid. In-situ polymerization was carried out at 65℃ for 2 h. After the reaction was completed, the mixture was washed and dried at 40℃ to obtain nano-SiO2 / UF composite outer wall. S5. PDA outer wall alkali-resistant layer coating: The nano SiO2 / UF composite outer wall was dispersed in Tris-HCl buffer (pH=8.5, 10mmol / L), and dopamine hydrochloride was added to a final concentration of 2g / L. The reaction was carried out at room temperature in the dark with stirring for 8h. At this time, the PMMA sacrificial layer was still intact, and the hygroscopic layer was doubly isolated by the UF wall and PMMA to prevent LiCl from deliquescing and swelling when it came into contact with water. After the reaction, the microspheres were centrifuged, washed quickly with deionized water, and the surface moisture of the microspheres was replaced with anhydrous ethanol. The microspheres were then immediately vacuum dried at 40℃ to obtain microspheres with a PDA layer on the surface. S6. Cavity formation: Disperse microspheres with PDA coating on the surface in acetone, stir at room temperature for 4-6 hours, replace with fresh acetone every 2 hours to dissolve and remove the PMMA sacrificial layer, centrifuge, wash, and vacuum dry at 35°C to obtain the final microcapsule product.
[0014] Preferably, in S4, the molar ratio of urea to formaldehyde is 1:2.
[0015] This invention also provides the application of temperature and humidity adaptive microcapsules in coral reef sand cementitious binders.
[0016] Preferably, the microcapsules are added at 6% to 8% of the mass of the coral reef sand cementitious binder, and the microcapsules include small-diameter capsules and medium-diameter capsules, with a mass ratio of 4 to 5:2 to 3; the coral reef sand cementitious binder also includes large-diameter capsules, with the large-diameter capsules added at 2% to 3% of the mass of the coral reef sand cementitious binder.
[0017] The large-diameter capsules have a particle size range of 300~800μm and are filled with epoxy resin, which is distributed in the macropores and aggregate interface. The large-diameter capsules are easily cut by cracks, but the epoxy resin can fill the large cracks and macropores to achieve repair. The medium-diameter capsules mainly contain phase change materials, which are evenly distributed in the cement stone matrix to balance the temperature, buffer temperature fluctuations, and inhibit thermal shrinkage cracks. The small-diameter capsules have a particle size range of 50~100μm and mainly contain hygroscopic agents, which are filled in the capillaries and micropores to form a humidity conduction network on the matrix surface. They absorb excess moisture and release it slowly to achieve internal curing and reduce drying shrinkage. The acid and alkali resistant barrier wall material layer effectively blocks the erosion of alkaline cement matrix and seawater, protects the integrity of the microcapsule structure, and ensures long-term service stability.
[0018] Preferably, the coral reef sand cement binder further includes carbon nanotubes and basalt fibers. The amount of carbon nanotubes is 0.04% of the mass of the coral reef sand cement binder, and the amount of basalt fibers is 0.42% of the mass of the coral reef sand cement binder. Carbon nanotubes (CNTs) fill nanoscale pores, improving matrix density, while basalt fibers provide bridging, controlling crack width and ensuring that the crack width is within the effective repair range of the microcapsules.
[0019] The coral reef sand cement binder is used in South China Sea island and reef engineering, and the microcapsules simultaneously play a dual role in temperature and humidity regulation. Temperature control: When the ambient temperature rises, the phase change core material melts and absorbs heat, reducing the peak temperature inside the concrete; when the ambient temperature drops, the phase change core material solidifies and releases heat, slowing down the cooling rate; thus buffering the temperature fluctuations inside the concrete and inhibiting the formation of thermal shrinkage cracks. Humidity control: When the internal humidity of the concrete is too high, the outer hydrophilic desiccant absorbs the excess moisture; when the internal humidity is insufficient, the desiccant slowly releases moisture to achieve internal curing; at the same time, it reduces the pore water content, reduces the transmission path of corrosive media such as chloride ions, and improves the resistance to seawater erosion.
[0020] Therefore, the present invention employs the above-mentioned temperature and humidity adaptive microcapsule, its preparation method, and its application, and the beneficial effects are as follows: Dual temperature and humidity control, synergistic functional enhancement: Through a four-layer core-shell structure design, the inner layer of hydrophobic phase change material regulates temperature, while the outer layer of hydrophilic hygroscopic agent regulates humidity. The barrier shell layer achieves two-phase isolation, solving the technical problem that hydrophilic and hydrophobic materials cannot coexist. The two functions do not interfere with each other and work synergistically, while suppressing thermal shrinkage cracks and drying shrinkage cracks. At the same time, the PMMA sacrificial layer acts as a temporary isolation barrier, dissolving out of the cavity after all aqueous phase and acid-base reactions are completed, protecting the inner phase change core and hygroscopic layer from the influence of the external environment throughout the process, resulting in high utilization of functional materials.
[0021] Enhanced corrosion resistance: Hydrophilic hygroscopic agents regulate pore humidity and reduce saturated water content, thereby lowering the transport rate of corrosive media such as chloride ions and sulfates; phase change materials buffer temperature stress and reduce crack formation; microcapsules of large, medium, and small particle sizes are compounded in a graded manner to perform repair, temperature regulation, and humidity regulation functions respectively, forming a three-dimensional functional network that highly matches the pore distribution characteristics of the cement matrix. The survival rate and efficiency of the microcapsules are greatly improved. The synergistic effect of crack repair, temperature regulation, humidity regulation, and alkali corrosion protection reduces the probability of problems such as drying shrinkage, thermal shrinkage, cracks, seawater erosion, and acid and alkali corrosion in coral reef sand cementitious structures, significantly improving the durability and service life of marine engineering structures.
[0022] The process is simple and can be mass-produced: It adopts the in-situ polymerization method to prepare in steps. The process is mature, the parameters are controllable, and it is easy to realize industrial mass production.
[0023] Wide range of applications: It is not only suitable for coral reef sand cement binders, but can also be extended to various systems such as ordinary concrete, thermal insulation mortar, and self-healing cement-based materials. It is especially suitable for marine engineering, pavement engineering, underground engineering and other scenarios with large temperature differences and drastic humidity changes.
[0024] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0025] Figure 1 This is a schematic diagram of the structure of a temperature and humidity adaptive microcapsule, its preparation method, and application embodiments of the present invention.
[0026] Figure Labels 1. Hydrophobic phase change core material layer; 2. Expansion cavity layer; 3. Hydrophilic moisture-absorbing intermediate layer; 4. Acid and alkali resistant barrier wall material layer. Detailed Implementation
[0027] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments.
[0028] Unless otherwise defined, the technical or scientific terms used in this invention shall have the ordinary meaning as understood by one of ordinary skill in the art to which this invention pertains.
[0029] like Figure 1 As shown, the temperature and humidity adaptive microcapsule of the present invention includes, from the inside out, a hydrophobic phase change core material layer 1, an expansion cavity layer 2, a hydrophilic and moisture-absorbing intermediate layer 3, and an acid and alkali resistant barrier wall material layer 4.
[0030] Example 1 A temperature and humidity adaptive microcapsule, specifically a medium-sized capsule with an average particle size of approximately 210 μm, is prepared as follows: (1) Preparation of hydrophobic phase change core material layer 1: 22g of n-octadecane was heated to 38℃ to melt, and Tween 80 (emulsifier) of 3% of the mass of n-octadecane was added. 110g of deionized water was added and dispersed at 4000rpm for 8min to form an O / W emulsion. Melamine-formaldehyde prepolymer (melamine:formaldehyde = 1:3) was added and the pH was adjusted to 5.2 with acetic acid. Polycondensation was carried out at 60℃ and 400rpm for 2h. After the reaction was completed, the mixture was washed with deionized water, filtered, and vacuum dried at 40℃ to obtain phase change core microspheres with MF as the wall (as the core template) with an average particle size of about 150μm. (2) PMMA sacrificial layer coating to obtain expansion cavity layer 2: The phase change core microspheres were immersed in 1% SDS (sodium dodecyl sulfonate) solution and stirred for 30 min to make the surface hydrophilic to adsorb surfactants; the phase change core microspheres were collected by centrifugation and dispersed in deionized water (solid content 10%), methyl methacrylate (MMA, 30% of the mass of microspheres) monomer and crosslinking agent ethylene glycol dimethacrylate (0.5 wt% of the mass of MMA) were added, potassium persulfate initiator (1% of the mass of MMA) was added, and the reaction was carried out at 55℃ for 5 h. By controlling the amount of monomer and the reaction time, a PMMA sacrificial layer with a thickness of about 4 μm (corresponding to the subsequent cavity thickness) was obtained. After the reaction was completed, the microspheres were washed by centrifugation and dried at 40℃ to obtain PMMA@phase change core microspheres. (3) Preparation of hydrophilic and hygroscopic intermediate layer 3: Sodium montmorillonite was dispersed in water (solid content 5%), and lithium chloride solution (LiCl loading 25%, based on the mass of sodium montmorillonite) was added and stirred for 2 hours for adsorption; polyvinyl alcohol binder was added to prepare hygroscopic slurry (final concentration of PVA was 3wt%); PMMA@phase change core microspheres were added to the slurry and gently stirred for 30 minutes. The microspheres were collected by filtration and placed in a sealed container containing 2% glutaraldehyde HCl solution (pH 2~3). The microspheres were crosslinked at room temperature for 15 minutes to allow PVA to crosslink in situ on the surface of the microspheres to form a water-insoluble bonding network. At the same time, montmorillonite and LiCl were fixed. The residual glutaraldehyde was removed by washing with anhydrous ethanol and then dried under vacuum at 40°C to obtain hygroscopic intermediate layer microspheres. (4) Preparation of nano-SiO2 reinforced UF wall: Urea and formaldehyde were mixed at a molar ratio of 1:2, the pH was adjusted to 8 with triethanolamine, and the reaction was carried out at 70℃ for 1 h to obtain urea-formaldehyde resin prepolymer. 5% nano-SiO2 was added and ultrasonically dispersed for 30 min. Moisture-absorbing intermediate layer microspheres were added to the prepolymer, stirred and dispersed, the pH was slowly adjusted to 2.5 with hydrochloric acid, and in-situ polymerization was carried out at 65℃ for 2 h. After the reaction was completed, the mixture was washed and dried at 40℃ to obtain nano-SiO2 / UF composite outer wall. (5) Preparation of acid and alkali resistant barrier wall material layer 4: The nano-SiO2 / UF composite outer wall was dispersed in Tris-HCl buffer (pH=8.5, 10mmol / L). The concentration of the nano-SiO2 / UF composite outer wall was about 50g / L. Dopamine hydrochloride was added to a final concentration of 2g / L. The reaction was stirred at room temperature in the dark for 8h. At this time, the PMMA sacrificial layer was still intact. The hygroscopic layer was doubly isolated by the UF wall and PMMA to prevent LiCl from deliquescing and swelling when it came into contact with water. After the reaction, the microspheres were centrifuged, washed quickly with deionized water, and the surface moisture of the microspheres was replaced with anhydrous ethanol. The microspheres were immediately vacuum dried at 40℃ to obtain microspheres with a PDA layer on the surface. (6) Cavity formation: Disperse microspheres with PDA layer on the surface in acetone, stir at room temperature for 6 hours, replace with fresh acetone every 2 hours, dissolve and remove PMMA sacrificial layer, centrifuge and wash, and vacuum dry at 35°C to obtain the final microcapsule product.
[0031] Tests showed that the phase change enthalpy was 128 J / g and the moisture absorption ratio was 15 times (by its own mass). After soaking in NaOH solution at pH 13 for 7 days, the phase change enthalpy retention rate was 86.2% and the moisture absorption ratio retention rate was 81.5%. After soaking in HCl solution at pH 1 for 7 days, the phase change enthalpy retention rate was 84.7% and the moisture absorption ratio retention rate was 79.3%.
[0032] Example 2 A temperature and humidity adaptive microcapsule, specifically a small-diameter capsule with an average particle size of approximately 75 μm, is prepared as follows: (1) Preparation of hydrophobic phase change core material layer 1: 12g of n-octadecane was heated to 38℃ to melt, and Tween 80 (emulsifier) of 6% of the mass of n-octadecane was added. 110g of deionized water was added and dispersed at 6000rpm for 10min to form an O / W emulsion. Melamine-formaldehyde prepolymer (melamine:formaldehyde = 1:3) was added and the pH was adjusted to 5.2 with acetic acid. Polycondensation was carried out at 60℃ and 400rpm for 2h. After the reaction was completed, the mixture was washed with deionized water, filtered, and vacuum dried at 40℃ to obtain phase change core microspheres with MF as the wall (as the core template) with an average particle size of about 150μm. (2) PMMA sacrificial layer coating to obtain expansion cavity layer 2: The phase change core microspheres were immersed in 1% SDS (sodium dodecyl sulfonate) solution and stirred for 30 min to make the surface hydrophilic to adsorb surfactants; the phase change core microspheres were collected by centrifugation and dispersed in deionized water (solid content 10%), methyl methacrylate (MMA, 30% of the mass of microspheres) monomer and crosslinking agent ethylene glycol dimethacrylate (0.5 wt% of the mass of MMA) were added, potassium persulfate initiator (1% of the mass of MMA, added in 3~5 batches) was added, and the reaction was carried out at 55℃ for 5 h. By controlling the amount of monomer and the reaction time, a PMMA sacrificial layer with a thickness of about 1.4 μm (corresponding to the subsequent cavity thickness) was obtained. After the reaction was completed, the microspheres were washed by centrifugation and dried at 40℃ to obtain PMMA@phase change core microspheres; (3) Preparation of hydrophilic and hygroscopic intermediate layer 3: Sodium montmorillonite was dispersed in water (solid content 5%), and lithium chloride solution (LiCl loading 25%, based on the mass of sodium montmorillonite) was added and stirred for 2 hours for adsorption; polyvinyl alcohol binder was added to prepare hygroscopic slurry (final concentration of PVA was 3wt%); PMMA@phase change core microspheres were added to the slurry and gently stirred for 30 minutes. The microspheres were collected by centrifugation and placed in a sealed container containing 2% glutaraldehyde in HCl solution (pH 2~3). The microspheres were crosslinked at room temperature for 15 minutes to allow PVA to crosslink in situ on the surface of the microspheres to form a water-insoluble bonding network, while fixing montmorillonite and LiCl. The residual glutaraldehyde was removed by washing with anhydrous ethanol and then dried under vacuum at 40°C to obtain hygroscopic intermediate layer microspheres. (4) Preparation of nano-SiO2 reinforced UF wall: Urea and formaldehyde were mixed at a molar ratio of 1:2, the pH was adjusted to 8 with triethanolamine, and the reaction was carried out at 70℃ for 1 h to obtain urea-formaldehyde resin prepolymer. 5% nano-SiO2 was added and ultrasonically dispersed for 30 min. Moisture-absorbing intermediate layer microspheres were added to the prepolymer, stirred and dispersed, the pH was slowly adjusted to 2.5 with hydrochloric acid, and in-situ polymerization was carried out at 65℃ for 2 h. After the reaction was completed, the mixture was washed and dried at 40℃ to obtain nano-SiO2 / UF composite outer wall. (5) Preparation of acid and alkali resistant barrier wall material layer 4: The nano-SiO2 / UF composite outer wall was dispersed in Tris-HCl buffer (pH=8.5, 10mmol / L). The concentration of the nano-SiO2 / UF composite outer wall was about 50g / L. Dopamine hydrochloride was added to a final concentration of 2g / L. The reaction was stirred at room temperature in the dark for 8h. At this time, the PMMA sacrificial layer was still intact. The hygroscopic layer was doubly isolated by the UF wall and PMMA to prevent LiCl from deliquescing and swelling when it came into contact with water. After the reaction, the microspheres were centrifuged, washed quickly with deionized water, and the surface moisture of the microspheres was replaced with anhydrous ethanol. The microspheres were immediately vacuum dried at 40℃ to obtain microspheres with a PDA layer on the surface. (6) Cavity formation: Disperse microspheres with PDA layer on the surface in acetone, stir at room temperature for 4 hours, replace with fresh acetone every 2 hours, dissolve and remove PMMA sacrificial layer, centrifuge and wash, and vacuum dry at 35°C to obtain the final microcapsule product.
[0033] Tests showed that the moisture absorption ratio was 25 times (its own weight); after soaking in NaOH solution at pH=13 for 7 days, the phase change enthalpy retention rate was 86.2%, and the moisture absorption ratio retention rate was 83.2%.
[0034] Example 3 A coral reef sand cement binder comprises 0.4g carbon nanotubes (CNTs), 4.2g basalt fiber, 45g medium-sized capsules from Example 1, 30g large-sized capsules, 25g small-sized capsules from Example 2, 115.4g cement, 232g coral reef sand, 448g crushed stone, and 100g water. The above components are dry-mixed for 2 minutes, then water is added and stirred for 3 minutes. After molding and curing, the finished product is obtained.
[0035] Among them, based on the variable rotation speed-time coefficient method, a system of linear equations was established to solve for the mass ratio of three types of microcapsules: large-diameter capsules, medium-diameter capsules, and small-diameter capsules, and the final mass ratio was determined to be 30:45:25. The preparation method of large-diameter capsules is as follows: (1) Weigh 28g of E-51 epoxy resin, add 3% of the mass of epoxy resin of composite emulsifier (sodium dodecylbenzene sulfonate: polyvinyl alcohol = 2:1), add 135g of deionized water, disperse in a high-speed dispersion homogenizer at 800r / min for 30min to form a stable O / W type emulsion. (2) Preparation of urea-formaldehyde resin prepolymer: 20g urea, 13.5g of 37% formaldehyde solution (n=1:2), adjust pH=9 with triethanolamine, reflux and stir at 70℃ for 1h; (3) In-situ polymerization: O / W type emulsion and prepolymer are mixed, pH is adjusted to 3.0 with ammonium chloride, and the mixture is stirred at varying speeds (stirred at 150 rpm for 2 hours and then at 250 rpm for 1 hour), and reacted at 70℃ for 3 hours; (4) PDA coating: After centrifugation and washing, disperse in Tris-HCl buffer (pH=8.5), add dopamine hydrochloride to a final concentration of 2 g / L, and react at room temperature in the dark for 8 h; (5) Post-processing: washing, filtering, and vacuum drying at 40℃ to obtain large-particle-size epoxy repair microcapsules.
[0036] Comparative Example 1 The difference from Example 3 is that no large-particle-size capsules, medium-particle-size capsules, or small-particle-size capsules are added, while the other components remain unchanged.
[0037] Comparative Example 2 The difference from Example 3 is that carbon nanotubes, basalt fibers, large-diameter capsules, medium-diameter capsules, and small-diameter capsules are not added, while the other components remain unchanged.
[0038] Comparative Example 3 The difference from Example 3 is that carbon nanotubes and basalt fibers are not added, and the large-diameter capsules, medium-diameter capsules and small-diameter capsules are replaced with ordinary phase change microcapsules (paraffin core + UF wall) at a dosage of 10%.
[0039] Test 1. The coral reef sand cement binders of Example 3 and Comparative Examples 1 to 3 were prepared into samples, and their mechanical properties and drying shrinkage properties were tested. The results are shown in Table 1.
[0040] Table 1. Changes in compressive strength and shrinkage.
[0041] 2. Samples were prepared from the coral reef sand cement binders of Example 3 and Comparative Examples 1-3. Temperature regulation performance of the coral reef sand cement binders was tested under simulated summer sunlight. The results are shown in Table 2.
[0042] Table 2 Temperature Regulation Changes
[0043] 3. Samples were prepared from the coral reef sand cement binders of Example 3 and Comparative Examples 1-3, and the alkali corrosion resistance and chloride ion permeation resistance of the coral reef sand cement binders were tested. The results are shown in Table 3.
[0044] Table 3. Changes in alkali corrosion resistance and chloride ion permeability over 90 days.
[0045] As shown in Tables 1-3, ordinary temperature and humidity capsules without alkali-resistant layers can achieve dual control of temperature and humidity, but the capsule wall hydrolyzes under long-term strong alkaline and seawater environments, resulting in insufficient long-term durability. In contrast, the moisture-absorbing layer of this invention continuously supplies water for internal curing, resulting in more complete cement hydration. The phase change material alleviates thermal cracking, and the dual effect enhances the matrix density. The dense PDA membrane on the outer wall seals the surface capillaries, reducing internal pore connectivity and further improving matrix density. The three-graded particles fill the large, medium, and small pores of coral reef sand, increasing strength by nearly 30%. The combination of temperature and humidity control with repair and multi-layer sealing creates a denser pore network, minimizing chloride ion penetration, making it suitable for the service environment of South China Sea island and reef engineering projects.
[0046] Therefore, the present invention employs the above-mentioned temperature and humidity adaptive microcapsule and its preparation method and application to achieve crack repair, temperature control, humidity control and alkali corrosion resistance, and through the gradation ratio, it is suitable for high corrosion and long-term service scenarios on islands and reefs in the South China Sea.
[0047] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A temperature and humidity adaptive microcapsule, characterized in that: The microcapsules include medium-sized and small-sized capsules. The medium-sized capsules have a particle size range of 100-300 μm, and the small-sized capsules have a particle size range of 50-100 μm. Both the medium-sized and small-sized capsules have a four-layer core-shell structure. The four-layer core-shell structure includes, from the inside out, a hydrophobic phase change core material layer, an expansion cavity layer, a hydrophilic and hygroscopic intermediate layer, and an acid and alkali resistant barrier wall material layer. The volume of the expansion cavity layer is 10-15% of the total volume of the microcapsules.
2. The temperature and humidity adaptive microcapsule according to claim 1, characterized in that: The hydrophobic phase change core layer includes a phase change material, which is n-octadecane; the hydrophilic hygroscopic intermediate layer includes a hydrophilic hygroscopic agent, which is a composite of lithium chloride and montmorillonite; the acid and alkali resistant barrier wall material layer is a modified urea-formaldehyde resin.
3. The temperature and humidity adaptive microcapsule according to claim 2, characterized in that, The modified urea-formaldehyde resin specifically comprises: The outer layer of the urea-formaldehyde resin wall material is coated with one or more of polydopamine and graphene oxide; the interior of the urea-formaldehyde resin is doped with one or more of nano-SiO2 or carbon fiber.
4. A method for preparing temperature and humidity adaptive microcapsules as described in any one of claims 1 to 3, characterized in that, Includes the following steps: S1. Preparation of phase change core template microspheres: octadecane was heated and melted, Tween 80 was added, and the mixture was dispersed at 4000~6000 rpm for 8~10 min to form an O / W emulsion. Melamine-formaldehyde prepolymer was added, and the pH was adjusted to 5.2~5.
5. After the polycondensation reaction was completed, the mixture was washed, filtered, and vacuum dried to obtain phase change core microspheres. S2, PMMA sacrificial layer coating: The phase change core microspheres obtained in S1 were immersed in sodium dodecyl sulfonate solution, then the phase change core microspheres were dispersed in deionized water, methyl methacrylate monomer and ethylene glycol dimethacrylate were added, potassium persulfate initiator was added, and the reaction was carried out at 50~55℃ for 4~6h. After the reaction was completed, the microspheres were centrifuged, washed, and dried to obtain PMMA@phase change core microspheres. S3, Moisture-absorbing intermediate layer coating: Sodium-based montmorillonite is dispersed in water, lithium chloride solution is added, and the mixture is stirred for adsorption; polyvinyl alcohol binder is added to prepare a moisture-absorbing slurry, PMMA@phase change core microspheres obtained in S2 are added to the slurry, stirred, and the microspheres are collected by filtration or centrifugation, transferred to an HCl solution containing 2% glutaraldehyde, crosslinked at room temperature, washed with anhydrous ethanol to remove residual glutaraldehyde, and vacuum dried to obtain moisture-absorbing intermediate layer microspheres; S4. Preparation of nano-SiO2 reinforced UF wall: Urea and formaldehyde are mixed and reacted to obtain urea-formaldehyde resin prepolymer, and nano-SiO2 is added and ultrasonically dispersed evenly; the hygroscopic intermediate layer microspheres obtained in S3 are added to the prepolymer, stirred and dispersed, polymerized in situ, washed and dried after the reaction is completed to obtain nano-SiO2 / UF composite outer wall. S5, PDA outer wall alkali resistant layer coating: The nano SiO2 / UF composite outer wall obtained in S4 was dispersed in Tris-HCl buffer, and dopamine hydrochloride was added to a final concentration of 2 g / L. The reaction was carried out at room temperature in the dark by stirring. After the reaction, the microspheres were centrifuged, washed quickly with deionized water, and the surface water of the microspheres was replaced with anhydrous ethanol. The microspheres were then vacuum dried to obtain microspheres with a PDA layer on the surface. S6. Cavity formation: Disperse the microspheres with PDA layer on the surface obtained in S5 in acetone, stir at room temperature for 4-6 hours, replace with fresh acetone every 2 hours, centrifuge, wash, and vacuum dry to obtain the final microcapsule product.
5. The method for preparing a temperature and humidity adaptive microcapsule according to claim 4, characterized in that, In S3, sodium montmorillonite is dispersed in water to obtain a sodium montmorillonite-water solution with a solid content of 5%. Then, lithium chloride solution is added, and the lithium chloride loading is 25% based on the mass of sodium montmorillonite.
6. The method for preparing a temperature and humidity adaptive microcapsule according to claim 4, characterized in that, In S4, the molar ratio of urea to formaldehyde is 1:
2.
7. The application of a temperature and humidity adaptive microcapsule as described in any one of claims 1 to 3, or a microcapsule prepared by the method of preparing a temperature and humidity adaptive microcapsule as described in any one of claims 4 to 6, in a coral reef sand cement binder.
8. The application according to claim 7, characterized in that: The microcapsules are added at a rate of 6% to 8% of the mass of the coral reef sand cementitious binder. The microcapsules include small-diameter capsules and medium-diameter capsules, with a mass ratio of 4 to 5:2 to 3. The coral reef sand cementitious binder also includes large-diameter capsules, with a content of 2% to 3% of the mass of the coral reef sand cementitious binder.
9. The application according to claim 8, characterized in that: The large-diameter capsules have a particle size range of 300~800μm and are filled with epoxy resin.
10. The application according to claim 9, characterized in that: The coral reef sand cement binder also includes carbon nanotubes and basalt fibers.
